Electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2021566869
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-10-29
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-10-29
Smart Images

Figure 0007634181000004 
Figure 0007634181000005 
Figure 0007634181000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery. [Background technology]
[0002] 2. Description of the Related Art In recent years, non-aqueous electrolyte secondary batteries, which perform charging and discharging by transferring lithium ions between a positive electrode and a negative electrode, have been widely used as high-output, high-energy density secondary batteries.
[0003] Incidentally, a nail penetration test is a safety evaluation test for checking the resistance of a battery to an internal short circuit. The nail penetration test is a test in which, for example, a nail is penetrated into a battery to simulate an internal short circuit, and the degree of heat generation is examined to check the safety of the battery. In order to ensure the safety of the battery, it is important to suppress the heat generation of the battery when the battery is penetrated by the nail.
[0004] For example, Patent Document 1 discloses a technology for suppressing heat generation in a battery during a nail penetration test by disposing a coating layer containing a functional material selected from a phosphorus-containing compound, a nitrogen-containing compound, and an inorganic silicon compound on the surfaces of the positive and negative electrodes.
[0005] For example, Patent Document 2 discloses a technique for suppressing temperature rise during abnormal heat generation in a battery by disposing an intermediate layer containing a polyphosphate between a positive electrode and a negative electrode. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2017-534138 A [Patent Document 2] Patent No. 6249399 Summary of the Invention
[0007] As in Patent Documents 1 and 2, when a coating layer of a functional material is provided on the surface of the electrode plate or an intermediate layer of a polyphosphate is provided, there is a problem that these layers act as resistors, increasing the battery resistance.
[0008] An electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a current collector, an active material layer formed on the current collector, and an aggregate of filler particles present in an island shape on a surface of the active material layer, the filler particles being compound particles containing at least one of phosphorus, silicon, boron, nitrogen, potassium, sodium, and bromine, and having a transformation point in the range of 180°C to 1000°C at which the filler particles transform from a solid phase to a liquid phase or are thermally decomposed.
[0009] A non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode and a negative electrode, and at least one of the positive electrode and the negative electrode is an electrode for the non-aqueous electrolyte secondary battery.
[0010] According to the present disclosure, it is possible to suppress heat generation in a battery during a nail penetration test while suppressing an increase in battery resistance. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the configuration of an electrode according to the present embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0013] Fig. 1 is a schematic cross-sectional view showing an example of the configuration of an electrode according to the present embodiment. An electrode 60 shown in Fig. 1 is an electrode for a non-aqueous electrolyte secondary battery, and is used for at least one of the positive electrode and the negative electrode of the non-aqueous electrolyte secondary battery.
[0014] 1 includes a current collector 62, an active material layer 64 formed on the current collector 62, and aggregates 66 of filler particles present in an island shape on the surface of the active material layer 64. That is, the surface structure of the electrode 60 is a sea-island structure having a sea region on the surface of the active material layer and island regions of the aggregates 66 of the filler particles. The aggregates 66 are a collection of single or multiple filler particles.
[0015] The filler particles constituting the aggregate 66 are compound particles containing at least one of phosphorus, silicon, boron, nitrogen, potassium, sodium, and bromine, and have a transformation point in the range of 180°C to 1000°C at which they transform from a solid phase to a liquid phase or decompose thermally.
[0016] By using the electrode for a non-aqueous electrolyte secondary battery according to this embodiment, the rise in the battery temperature during the nail penetration test is suppressed. The mechanism is not fully clear, but the following is presumed. Due to the heat generated by the battery during the nail penetration test, that is, the heat generated by the battery when a nail is pierced into the battery to simulate an internal short circuit, the filler particles constituting the aggregate 66 transform from a solid phase to a liquid phase and flow on the surface of the active material layer 64, or extend on the surface of the active material layer 64 by thermal decomposition, forming a coating that covers the surface of the active material layer 64. Since the coating functions as a resistance component, the amount of short-circuit current flowing between the positive and negative electrodes via the nail is suppressed, and as a result, the rise in the battery temperature during the nail penetration test is also suppressed. The formation of the coating after the transformation of the filler particles into a liquid phase depends on the type of filler particles, but is due to, for example, a temperature rise above the melting point of the filler material, a heat fusion reaction, a dehydration condensation reaction, a thermal polymerization reaction, or the like.
[0017] In addition, according to the electrode for a non-aqueous electrolyte secondary battery of this embodiment, the increase in battery resistance is suppressed. During normal use when the battery is not abnormally heated, the aggregates 66 of the filler particles are made of a material with low lithium ion conductivity, and if they are present in a layered form, they will hinder the movement of lithium ions, causing an increase in battery resistance. However, since the aggregates 66 are in an island form in this embodiment, there are gaps between the aggregates 66, and ions such as lithium ions can easily pass through the gaps. Therefore, when the battery is charged and discharged, lithium ions move more smoothly between the positive and negative electrodes than when the entire surface of the active material layer 64 is covered with a coating layer of filler particles without any gaps, and it is considered that the increase in battery resistance is suppressed.
[0018] The constituent materials of the electrodes 60 will be described in further detail below.
[0019] The filler particles are compound particles containing at least one of phosphorus, silicon, boron, nitrogen, potassium, sodium, and bromine, and are not particularly limited as long as the transformation point at which the solid phase transforms into the liquid phase or the thermal decomposition occurs is in the range of 180°C to 1000°C. Examples of the filler particles include phosphoric acid compounds, silicic acid compounds, boric acid compounds, melamine compounds, potassium salt compounds, and sodium salt compounds. Examples of the phosphoric acid compounds include metal salts of phosphoric acid such as lithium phosphoric acid salt, sodium phosphoric acid salt, potassium phosphoric acid salt, calcium phosphoric acid salt, magnesium phosphoric acid salt, and aluminum phosphate, condensed phosphates such as ammonium polyphosphate, sodium tripolyphosphate, and melamine polyphosphate, and phosphoric acid esters such as trimethyl phosphate and triphenyl phosphate. Examples of the boric acid compound include metal borate salts such as sodium borate, potassium borate, calcium borate, magnesium borate, aluminum borate, and melamine borate, borate esters such as trimethyl borate, boron oxides, and condensed borates. Examples of the silicic acid compound include metal silicates such as sodium silicate, potassium silicate, calcium silicate, magnesium silicate, barium silicate, and manganese silicate. Examples of the melamine compound include melamine cyanurate, melamine pyrophosphate, ethylene dimelamine, trimethylene dimelamine, tetramethylene dimelamine, hexamethylene dimelamine, and 1,3-hexylene dimelamine. Examples of the potassium salt compound include potassium pyrosulfate (K 2 S 2 O 7 ), potassium citrate monohydrate (C 6 H 5 K 3 O 7 H 2Examples of the sodium salt compound include sodium carbonate. Among these, melamine polyphosphate, ammonium polyphosphate, sodium tripolyphosphate, sodium silicate, sodium borate, potassium citrate monohydrate, lithium metaphosphate, potassium dihydrogen phosphate, melamine cyanurate, potassium pyrosulfate, boron oxide, ethylene-1,2-bis(pentabromophenyl), ethylenebistetrabromophthalimide, potassium carbonate, and sodium carbonate are preferred.
[0020] The transformation point of the filler particles may be in the range of 180°C to 1000°C so that the filler particles appropriately transform from a solid phase to a liquid phase or undergo thermal decomposition due to heat generation in the battery during a nail penetration test, but is preferably in the range of 250°C to 600°C.
[0021] The coverage of the aggregates 66 with respect to the surface of the active material layer 64 is preferably 90% or less, more preferably 65% or less, in order to suppress an increase in battery resistance. The coverage of the aggregates 66 with respect to the surface of the active material layer 64 is preferably 5% or more in order to suppress an increase in battery temperature in a nail penetration test. The higher the coverage, the shorter the time it takes to form a coating layer that covers the surface of the active material layer 64 when the battery heats up, but this is accompanied by an increase in battery resistance, so an optimal configuration is required depending on the purpose. The coverage of the aggregates 66 is calculated as follows.
[0022] The coverage rate is obtained by performing elemental mapping of the electrode surface using SEM-EDX (Energy Dispersive X-ray spectrometry) or the like. For example, the coverage rate is obtained by distinguishing the island regions of the aggregates 66 from the sea regions of the active material layer surface using elemental mapping, and calculating the ratio of the area of the island regions to the total area of the island regions and the sea regions. As for the accuracy of elemental mapping, if there is a non-covered region of about 2 μm square, the sea regions and the island regions can be distinguished from each other.
[0023] 1000μm 2The number of aggregates 66 having an area of 1000 μm or less is preferably 80% or more, and more preferably 90% or more, of the total number of aggregates 66. 2 The greater the number of assemblies 66 having an area below this level, the greater the number and uniformity of the gaps between the assemblies 66 that serve as paths through which ions such as lithium ions can easily pass, thereby making it possible to suppress an increase in battery resistance.
[0024] The assembly 66 is 1 mm 2 It is preferable that there are 100 or more, and more preferable that there are 200 or more, per unit area. The more filler particles that make up aggregate 66, the more quickly the filler particles are transformed from a solid phase to a liquid phase or are thermally decomposed by heat generation in the battery during the nail penetration test, thereby coating the surface of active material layer 64, and therefore the increase in battery temperature during the nail penetration test can be effectively suppressed.
[0025] The average particle size of the filler particles constituting the aggregate 66 is preferably 0.1 μm to 20 μm, and more preferably in the range of 0.5 μm to 3 μm. The average particle size of the filler particles is determined as follows. First, 20 filler particles are randomly selected from an SEM image of the electrode surface. Next, the grain boundaries of the selected 20 filler particles are observed, the outer shapes of the filler particles are identified, the areas of the 20 filler particles are determined, and the average particle size of the filler particles is calculated from the average value of the areas.
[0026] The assembly 66 may contain a binder in addition to the filler particles. By containing a binder, the binding property between the filler particles and the binding property between the filler particles and the current collector 62 can be improved. The binder is not particularly limited, and examples thereof include polyvinylidene fluoride (PVdF), ethylene dimethacrylate, allyl methacrylate, t-dodecyl mercaptan, α-methylstyrene dimer, and methacrylic acid. Note that polyvinylidene fluoride (PVdF), ethylene dimethacrylate, allyl methacrylate, t-dodecyl mercaptan, α-methylstyrene dimer, and methacrylic acid can bond the electrode 60 to the separator 13 by applying pressure and / or heat to the assembly 66. The assembly 66 may also contain compound particles other than the filler particles. Examples of compound particles other than the filler particles include inorganic particles such as alumina, boehmite, and titania.
[0027] When the electrode 60 is used as a positive electrode, the current collector 62 serving as the positive electrode current collector can be, for example, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having such a metal disposed on the surface layer. Moreover, the active material layer 64 serving as the positive electrode active material layer contains a positive electrode active material, and preferably also contains a conductive material and a binder.
[0028] Examples of the positive electrode active material include lithium transition metal composite oxides. Specifically, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese composite oxide, lithium nickel cobalt composite oxide, etc. can be used. These lithium transition metal composite oxides may contain Al, Ti, Zr, Nb, B, W, Mg, Mo, etc.
[0029] As the conductive material, carbon powder such as carbon black, acetylene black, ketjen black, graphite, etc. may be used alone or in combination of two or more kinds.
[0030] Examples of the binder include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide-based resins, acrylic-based resins, polyolefin-based resins, etc. These may be used alone or in combination of two or more kinds.
[0031] An example of a method for producing a positive electrode will be described. First, a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, a solvent, etc. is applied onto a positive electrode current collector, the coating is dried, and then rolled to form a positive electrode active material layer on the positive electrode current collector. Next, a filler slurry containing filler particles, a binder, a solvent, etc. is prepared. Then, the prepared filler slurry is sprayed, dropped, transferred, or applied onto the positive electrode active material layer, and then dried to form an aggregate of filler particles present in an island shape on the surface of the positive electrode active material layer. Examples of the solvent contained in the slurry include water, N-methyl-2-pyrrolidone (NMP), ethanol, etc.
[0032] The island-shaped aggregate can be obtained, for example, by adjusting the amount of filler particles and solvent contained in the filler slurry and controlling the amount of the filler slurry sprayed, dropped, or applied. Alternatively, the island-shaped aggregate can be obtained, for example, by placing a masking sheet or the like having a plurality of through holes of a predetermined size on the positive electrode active material layer and spraying, dropping, or applying the filler slurry from above the placed masking sheet.
[0033] When the electrode 60 is used as a negative electrode, the current collector 62 serving as the negative electrode current collector can be, for example, a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having such a metal disposed on its surface. Moreover, the active material layer 64 serving as the negative electrode active material layer preferably contains a negative electrode active material and also contains a binder or the like.
[0034] As the negative electrode active material, a carbon material capable of absorbing and releasing lithium ions can be used, and in addition to graphite, non-graphitizable carbon, graphitizable carbon, fibrous carbon, coke, carbon black, etc. Furthermore, as a non-carbon-based material, silicon, tin, and alloys and oxides mainly containing these can be used.
[0035] Examples of the binder include fluorine-based resin, PAN, polyimide-based resin, acrylic resin, polyolefin-based resin, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or a salt thereof, polyacrylic acid (PAA) or a salt thereof (PAA-Na, PAA-K, etc., or a partially neutralized salt), polyvinyl alcohol (PVA), etc. These may be used alone or in combination of two or more kinds.
[0036] An example of a method for producing a negative electrode is described below. First, a negative electrode mixture slurry containing a negative electrode active material, a binder, a solvent, etc. is applied onto a negative electrode current collector, the coating is dried, and then rolled to form a negative electrode active material layer on the negative electrode current collector. Next, a filler slurry containing filler particles, a binder, a solvent, etc. is sprayed, dropped, or applied onto the negative electrode active material layer, and then dried to form an aggregate of filler particles present in an island shape on the surface of the negative electrode active material layer. The method for obtaining the island-shaped aggregate is as described above.
[0037] An example of the nonaqueous electrolyte secondary battery according to this embodiment will be described below.
[0038] FIG. 2 is a schematic cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment. The nonaqueous electrolyte secondary battery 10 shown in FIG. 2 includes a wound electrode body 14 formed by winding a positive electrode 11 and a negative electrode 12 with a separator 13 therebetween, a nonaqueous electrolyte, insulating plates 18 and 19 respectively arranged above and below the electrode body 14, and a battery case 15 for accommodating the above-mentioned members. The battery case 15 is composed of a bottomed cylindrical case body 16 and a sealing body 17 for closing an opening of the case body 16. Note that, instead of the wound electrode body 14, an electrode body of another form may be applied, such as a laminated electrode body formed by alternately stacking positive and negative electrodes with a separator interposed therebetween. In addition, examples of the battery case 15 include a cylindrical, square, coin-shaped, button-shaped, or other metal case, and a resin case formed by laminating a resin sheet (so-called laminate type).
[0039] The case body 16 is, for example, a cylindrical metal container with a bottom. A gasket 28 is provided between the case body 16 and the sealing body 17 to ensure airtightness inside the battery. The case body 16 has a protruding portion 22 that supports the sealing body 17, for example, a part of the side surface of the case body 16 protruding inward. The protruding portion 22 is preferably formed in an annular shape along the circumferential direction of the case body 16, and supports the sealing body 17 on its upper surface.
[0040] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between each of their peripheral edges. When the internal pressure of the secondary battery 10 increases due to heat generation caused by an internal short circuit or the like, for example, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0041] 2, a positive electrode lead 20 attached to the positive electrode 11 extends through a through hole in an insulating plate 18 toward the sealing body 17, and a negative electrode lead 21 attached to the negative electrode 12 extends through the outside of an insulating plate 19 toward the bottom side of a case body 16. The positive electrode lead 20 is connected to the underside of a filter 23, which is the bottom plate of the sealing body 17, by welding or the like, and a cap 27, which is the top plate of the sealing body 17 and is electrically connected to the filter 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom surface of the case body 16 by welding or the like, and the case body 16 serves as a negative electrode terminal.
[0042] The above-mentioned electrode 60 is applied to at least one of the positive electrode 11 and the negative electrode 12. The separator 13 is made of a porous sheet or the like having ion permeability and insulation. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator 13 is preferably made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator 13 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. The separator 13 may also be a multilayer separator including a polyethylene layer and a polypropylene layer, and may be made of a material such as an aramid resin or ceramic applied to the surface of the separator 13.
[0043] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, and mixtures of two or more of these. The non-aqueous solvent may contain a halogen-substituted compound in which at least a portion of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. The electrolyte salt may include, for example, LiPF 6 Lithium salts such as
[0044] Next, an embodiment will be described.
[0045] <Example> <Example 1> [Preparation of positive electrode] LiNi 0.82 Co 0.15 Al 0.03O 2 100 parts by weight of the positive electrode active material represented by the formula (I), 1 part by weight of acetylene black (AB), and 1 part by weight of polyvinylidene fluoride (PVdF) were mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to both sides of a positive electrode current collector made of aluminum foil and dried. This was cut into a predetermined electrode size and rolled using a roller to form a positive electrode active material layer on both sides of the positive electrode current collector. Next, 5 parts by weight of melamine polyphosphate particles and 1 part by weight of polyvinylidene fluoride (PVdF) were mixed, and 100 mL of N-methyl-2-pyrrolidone (NMP) was added to prepare a filler slurry. 100 mL of the filler slurry was applied to the positive electrode active material layer to a wet film thickness of 4 um and dried. This was the positive electrode of Example 1.
[0046] When the surface of the positive electrode of Example 1 was observed by SEM-EDX, it was confirmed that the aggregates of the melamine polyphosphate particles were in the form of islands, and the coverage of the aggregates of the melamine polyphosphate particles was 5%.
[0047] [Preparation of negative electrode] 100 parts by weight of graphite powder, 1 part by weight of carboxymethyl cellulose (CMC), and 1 part by weight of styrene-butadiene rubber (SBR) were mixed, and an appropriate amount of water was added to prepare a negative electrode composite slurry. Next, the negative electrode composite slurry was applied to both sides of a negative electrode current collector made of copper foil and dried. This was cut into a predetermined electrode size and rolled using a roller to form a negative electrode active material layer on both sides of the negative electrode current collector.
[0048] [Preparation of non-aqueous electrolyte] Lithium hexafluorophosphate (LiPF 6 ) was dissolved in water to a concentration of 1 mol / L to prepare a non-aqueous electrolyte.
[0049] [Preparation of non-aqueous electrolyte secondary battery] (1) A positive electrode lead was attached to the positive electrode current collector, and a negative electrode lead was attached to the negative electrode current collector. After that, the positive and negative electrodes were wound with a polyethylene separator interposed between them to prepare a wound type electrode body. (2) Insulating plates were placed above and below the electrode body, the negative electrode lead was welded to the case body, and the positive electrode lead was welded to the sealing member, and the electrode body was housed within the case body. (3) After the non-aqueous electrolyte was injected into the case body under reduced pressure, the open end of the case body was sealed with a sealing body via a gasket, completing the non-aqueous electrolyte secondary battery.
[0050] <Example 2> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the preparation of the filler slurry, the amount of melamine polyphosphate particles added was 30 parts by weight, and 100 mL of the prepared filler slurry was applied to the positive electrode active material layer to a wet film thickness of 6 um. When the positive electrode surface of Example 2 was observed by SEM-EDX, it was confirmed that the aggregates of the melamine polyphosphate particles were island-shaped, and the coverage rate of the aggregates of the melamine polyphosphate particles was 65%.
[0051] <Example 3> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the preparation of the filler slurry, the amount of melamine polyphosphate particles added was 30 parts by weight, and 100 mL of the prepared filler slurry was applied to the positive electrode active material layer to a wet film thickness of 10 um. When the positive electrode surface of Example 3 was observed by SEM-EDX, it was confirmed that the aggregates of the melamine polyphosphate particles were in an island shape, and the coverage rate of the aggregates of the melamine polyphosphate particles was 90%.
[0052] <Examples 4 to 6> Except for replacing melamine polyphosphate particles with ammonium polyphosphate particles in the preparation of the filler slurry, nonaqueous electrolyte secondary batteries were fabricated in the same manner as in Example 1 for Example 4, in the same manner as in Example 2 for Example 5, and in the same manner as in Example 3 for Example 6. When the positive electrode surfaces of Examples 4 to 6 were observed by SEM-EDX, it was confirmed that the aggregates of ammonium polyphosphate particles were in the form of islands, and the coverage of the aggregates of ammonium polyphosphate particles was 5%, 65%, and 90%, respectively.
[0053] <Examples 7 to 9> In preparing the filler slurry, melamine polyphosphate particles were mixed with lithium metaphosphate (LiPO 3 ) n Except for replacing the lithium metaphosphate particles with lithium phosphate ...
[0054] <Examples 10 to 12> In preparing the filler slurry, melamine polyphosphate particles were mixed with sodium silicate (Na 2 SiO 3 Except for replacing sodium silicate particles with sodium silicate 20 particles, nonaqueous electrolyte secondary batteries were fabricated in the same manner as in Example 1 for Example 10, in the same manner as in Example 2 for Example 11, and in the same manner as in Example 3 for Example 12. When the positive electrode surfaces of Examples 10 to 12 were observed by SEM-EDX, it was confirmed that the aggregates of sodium silicate particles were in an island shape, and the coverage of the aggregates of sodium silicate particles was 5%, 65%, and 90%, respectively.
[0055] <Examples 13 to 15> In preparing the filler slurry, melamine polyphosphate particles were mixed with sodium borate (Na 2 B 4 O 7Except for replacing sodium borate particles with sodium borate particles, nonaqueous electrolyte secondary batteries were fabricated in the same manner as in Example 1 for Example 13, in the same manner as in Example 2 for Example 14, and in the same manner as in Example 3 for Example 15. When the positive electrode surfaces of Examples 13 to 15 were observed by SEM-EDX, it was confirmed that the aggregates of sodium borate particles were in an island shape, and the coverage of the aggregates of sodium borate particles was 5%, 65%, and 90%, respectively.
[0056] <Comparative Example 1> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that no filler slurry was used.
[0057] <Comparative Example 2> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the preparation of the filler slurry, the amount of melamine polyphosphate particles added was 30 parts by weight, and 100 mL of the prepared filler slurry was applied onto the positive electrode active material layer to a wet film thickness equivalent to 15 μm.
[0058] <Comparative Examples 3 to 6> In preparing the filler slurry, the melamine polyphosphate particles were replaced with ammonium polyphosphate particles in Comparative Example 3, with lithium metaphosphate particles in Comparative Example 4, with sodium silicate particles in Comparative Example 5, and with sodium borate particles in Comparative Example 6. Except for this, nonaqueous electrolyte secondary batteries were fabricated in the same manner as in Comparative Example 2.
[0059] When the surfaces of the positive electrodes of Comparative Examples 2 to 6 were observed by SEM-EDX, no island-shaped aggregates of filler particles were observed, and the coverage of the aggregates of filler particles was 100%.
[0060] [Nail penetration test] For the nonaqueous electrolyte secondary batteries of Examples 1 to 15 and Comparative Examples 1 to 6, a nail penetration test was carried out according to the following procedure. (1) In an environment of 25°C, the battery was charged at a constant current of 600 mA until the battery voltage reached 4.2 V, and then continued to be charged at a constant voltage until the current value reached 90 mA. (2) In an environment of 25°C, the tip of a round nail with a diameter of 2.7 mm was brought into contact with the center of the side of the battery charged in (1), and the round nail was thrust into the battery in the stacking direction of the electrode body at a speed of 1 mm / sec. Immediately after detecting a drop in the battery voltage due to an internal short circuit, thrusting of the round nail was stopped. (3) The battery surface temperature was measured one minute after the battery started to short circuit with the round nail. The measured temperatures were listed in Table 1 as the temperatures after the nail penetration test.
[0061] [Battery resistance] The battery resistance of the nonaqueous electrolyte secondary batteries of Examples 1 to 15 and Comparative Examples 1 to 6 was measured as follows. In a temperature environment of 25°C, the nonaqueous electrolyte secondary batteries were charged at a constant current of 0.3C until the battery voltage reached 4.2V, then charged at a constant voltage until the current value reached 0.05C, and then discharged at a constant current of 0.3C to set the SOC to 50%. Next, the voltage values were obtained when discharge currents of 0A, 0.1A, 0.5A, and 1.0A were applied for 10 seconds. DC-IR was calculated from the absolute value of the slope when the voltage value after 10 seconds for each discharge current value was linearly approximated by the least squares method, and this value was summarized in Table 1 as the battery resistance.
[0062] [Table 1]
[0063] As shown in Table 1, in all of Examples 1 to 15 in which an aggregate of filler particles was present in an island shape on the surface of the positive electrode active material layer, the battery temperature after the nail penetration test was lower than in Comparative Example 1 in which no filler particles were present on the surface of the positive electrode active material layer. Here, when the coverage rate of the aggregate of filler particles was taken as 100% as in Comparative Examples 2 to 6, the battery resistance increased significantly compared to Comparative Example 1. However, in Examples 1 to 15, the increase in battery resistance was suppressed more than in Comparative Examples 2 to 6. That is, in Examples 1 to 15, it was possible to suppress the heat generation of the battery in the nail penetration test while suppressing the increase in battery resistance.
[0064] <Examples 16 to 30> In Examples 16 to 30, nonaqueous electrolyte secondary batteries were fabricated in the same manner as in Examples 1 to 15, except that the filler slurry was applied onto the negative electrode active material layer instead of onto the positive electrode active material layer.
[0065] <Comparative Examples 7 to 10> In Comparative Examples 7 to 10, nonaqueous electrolyte secondary batteries were fabricated in the same manner as in Comparative Examples 2 to 6, except that the filler slurry was applied onto the negative electrode active material layer instead of onto the positive electrode active material layer.
[0066] The coverage of the aggregates of the filler particles in Examples 16 to 30 and Comparative Examples 7 to 10 is summarized in Table 2. In addition, the nonaqueous electrolyte secondary batteries of Examples 16 to 30 and Comparative Examples 7 to 10 were subjected to the above-mentioned nail penetration test and battery resistance measurement, and the results are summarized in Table 2.
[0067] [Table 2]
[0068] As can be seen from Table 2, the negative electrode side showed the same results as the positive electrode side. That is, in Examples 16 to 30, the increase in battery resistance was suppressed while heat generation in the battery during the nail penetration test was suppressed.
[0069] <Examples 31 to 40> In preparing the filler slurry, the melamine polyphosphate particles were replaced with sodium tripolyphosphate particles in Example 31 and potassium phosphate (KH 2 PO 4 ) particles, in Example 33 melamine cyanurate, and in Example 34 potassium pyrosulfate (K 2 S 2 O 7 In Example 35, instead of the boron oxide (B 2 O 3 ) particles, in Example 36 ethylene-1,2-bis(pentabromophenyl) particles, in Example 37 ethylenebistetrabromophthalimide particles, in Example 38 potassium citrate (C6 H 5 K 3 O 7 In Example 39, potassium carbonate (K 2 CO 3 In Example 40, sodium carbonate (Na 2 CO 3 A non-aqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the ZnO particles were replaced with ZnO particles.
[0070] The coverage of the aggregates of the filler particles in Examples 31 to 40 is summarized in Table 3. In addition, the nonaqueous electrolyte secondary batteries of Examples 31 to 40 were subjected to the above-mentioned nail penetration test and battery resistance measurement.
[0071] [Table 3]
[0072] In all of Examples 31 to 40, the battery temperature after the nail penetration test was lower than that of Comparative Example 1 in which no filler particles were present on the surface of the positive electrode active material layer. In addition, the battery resistance was higher than that of Comparative Example 1, but was comparable to that of Example 1. In other words, it can be said that Examples 31 to 40 were also able to suppress the heat generation of the battery during the nail penetration test while suppressing the increase in battery resistance. [Explanation of symbols]
[0073] 10 Nonaqueous electrolyte secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Battery case 16 Case body 17 Sealing body 18,19 Insulating plate 20 Positive lead 21 Negative lead 22 Overhang 23 Filters 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket 60 electrodes 62 Current collector 64 Active material layer 66 Aggregate
Claims
1. a current collector; an active material layer formed on the current collector; and an aggregate of filler particles present in an island shape on a surface of the active material layer, the filler particles are compound particles containing at least one of phosphorus, silicon, boron, nitrogen, potassium, sodium, and bromine, and have a transformation point at which they transform from a solid phase to a liquid phase or are thermally decomposed in the range of 180° C. to 1000° C.; the filler particles include at least one of melamine polyphosphate, ammonium polyphosphate, lithium metaphosphate, sodium silicate, sodium borate, sodium tripolyphosphate, potassium phosphate, melamine cyanurate, potassium pyrosulfate, ethylene-1,2-bis(pentabromophenyl), ethylene bistetrabromophthalimide, potassium citrate, potassium carbonate, and sodium carbonate; The assembly includes a binder, and the binder includes at least one of polyvinylidene fluoride (PVdF), ethylene dimethacrylate, allyl methacrylate, t-dodecyl mercaptan, α-methylstyrene dimer, and methacrylic acid.
2. 2 . The electrode for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the coverage of the surface of the active material layer with the aggregate is 90% or less.
3. 3. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the coverage of the surface of the active material layer with the aggregate is 5% or more.
4. 1000μm 2 4. The electrode for a nonaqueous electrolyte secondary battery according to claim 1, wherein the number of said assemblies having an area equal to or less than the above range is 80% or more of the total number of said assemblies.
5. The assembly is 1 mm 2 The electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein 100 or more particles are present per one particle.
6. 6. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the filler particles have an average particle size of 0.1 μm to 20 μm.
7. 7. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the filler particles contain boron oxide.
8. The electrode for a non-aqueous electrolyte secondary battery as described in claim 6, wherein the average particle size of the filler particles is 0.5 μm to 3 μm.
9. A positive electrode and a negative electrode are provided. A non-aqueous electrolyte secondary battery, wherein at least one of the positive electrode and the negative electrode is the electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Driving of display panel
JP1987049399A
Separator for battery and battery using the same
JP2005276503A
Positive electrode for nonaqueous electrolyte secondary battery
JP2009164014A
Lithium ion battery
JP2010192365A
Lithium secondary battery
JP2010238464A